Evidence-based non-residential waste analysis to support 3R strategies and food recovery hierarchy: a case study in Solok Selatan - Fauzi, Mhd.; Aziz, Rizki; Chyntia, Nanda; Titani, Fena Retyo; Afrianto, Andika Wahyu (Bioeksperimen: Jurnal Penelitian Biologi, 2026)
The amount of waste generation that increases without being accompanied by good waste management will cause pollution and decrease the aesthetic value of the environment. Non-residential waste originating from non-residential activities is also one of the contributors to waste entering the landfill. This study aims to analyze non-residential waste generation and composition as an evidence-based reference for each source in implementing the 3R concept and the Food Recovery Hierarchy (FRH). The number of sampling sets was determined at a minimum of 10% of each type of facility following SNI 19-3964-1994. Sampling was carried out on eight consecutive days with 14 sampling points in Area 1, 14 in Area 2, and 11 in Area 3. The total non-residential waste generation was 46.79 m³/day (9.49 tons/day). Organic waste dominated the composition, accounting for 35–37% as food waste, followed by plastic (24–29%) and paper (14–20%). The high proportion of biodegradable and recyclable materials indicates significant potential for composting, recycling, and food recovery strategies at the source level. Implementing source-level 3R and FRH approaches could substantially reduce landfill dependency and extend landfill lifespan. This study addresses a knowledge gap by linking source-level non-residential waste characterization with the practical implementation of the 3R concept and the Food Recovery Hierarchy. This study provides quantitative evidence to guide localized waste minimization strategies in non-residential sectors.